Bluetooth low energy for internet of things: review, challenges, and open issues - Mahmood A. Al-Shareeda; Murtaja Ali Saare; Selvakumar Manickam; Shankar Karuppayah (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
As a result of its ultra-low power consumption, simple development, sufficient network coverage, and rapid data transfer speed, Bluetooth low energy (BLE) has emerged as the standard communication standard for internet of things (IoT) nodes. Therefore, in this review paper introduces the concept of Bluetooth low energy for the internet of things (BLE-IoT) in terms of Bluetooth classic, Bluetooth version, applications for BLE-IoT, and new features of BLE-IoT. We then provide a taxonomy of literature reviews based on the parameter adjustment approach (e.g., advertiser side schemes, scanner side schemes, hybrid schemes) and collision avoidance approach (e.g., advertiser side schemes and scanner side schemes). Finally, we discuss research challenges and future opportunities for BLE-IoT.